1991
DOI: 10.1111/j.1600-0722.1991.tb01030.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fluoride amalgams on artificial recurrent enamel and root caries

Abstract: Abstract— The present study examined the effect of F‐containing amalgams on recurrent caries in vitro. Four amalgams were tested: A ‐ Conventional amalgam; B ‐ Amalgam A with 1% SnF2; C ‐ Non‐gamma‐2 amalgam; D ‐ Amalgam C with 1% SnF2. Twenty fillings from each amalgam were placed at the cementoenamel junction in sound extracted human teeth. The teeth were covered with varnish except for a 2‐mm‐wide zone around the fillings and immersed in separate vials containing dialyzed 15% gelatin gel, pH 4.2, for 17 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…This result is in agreement with those of other studies that demonstrated reduced demineralization along the cavity wall adjacent to the restoration of Synalloy fluore (Skartveit et al, 1991). Because the high-copper Tytin (NA) would have a corrosion rate similar to that of the highcopper Synalloy fluore (FA), microleakage may exert only a minimal influence on the difference in the lesion along the wall between the NA and FA groups.…”
Section: Fluoride Effectssupporting
confidence: 92%
See 1 more Smart Citation
“…This result is in agreement with those of other studies that demonstrated reduced demineralization along the cavity wall adjacent to the restoration of Synalloy fluore (Skartveit et al, 1991). Because the high-copper Tytin (NA) would have a corrosion rate similar to that of the highcopper Synalloy fluore (FA), microleakage may exert only a minimal influence on the difference in the lesion along the wall between the NA and FA groups.…”
Section: Fluoride Effectssupporting
confidence: 92%
“…Using a gel-type caries formation system, Skartveit et al (1991) compared demineralization adjacent to Synalloy and Synalloy fluore restorations. They demonstrated a significant inhibition of demineralization in the fluoridated amalgam group along the cavity walls, but not on the outer surfaces, both in root and in enamel.…”
Section: Fluoride Effectsmentioning
confidence: 99%
“…A similar study 127 , involving 18 Class V cavities in the buccal and lingual surfaces of 18 extracted premolars restored with a range of materials, concluded that restoration of cavities with glass-ionomer materials and fluoride-containing amalgam may be of great importance in the prevention of both secondary caries around the restorations and primary caries in surface enamel adjacent to the restoration. A further study 128 using an artificial caries model compared the effect of both fluoridated and non-fluoridated amalgams on the inhibition of enamel and root lesions in human extracted teeth. Protection was most evident with a high-copper silver amalgam containing 1% (wt) SnF 2 .…”
Section: Dental Amalgammentioning
confidence: 99%
“…Caries incidence is falling in many developed eountries (1-3), where placing amalgam fillings is the largest single item of treatment in dental praclice (4), ln several developing countries, earies prevalence is increasing (5-7), While for many people in such countries tlic need for restorative treatment may nol be met, placement of fillings can be expected to be the principal type of treatment, where manpower resources permit (7,8), Even where dental manpower resources are relatively good, this is not a very successful therapy: about 5O' !^i of amalgam fillings are replaced within 5 yr in Scotland (9), Seeondary caries is a frequent cause of failure of amalgam fillings (10, 11), Amalgam whieh contains fluoride has been available for many years (12), Fluoride is known to be released from sueh amalgam both in vitro (13) and in vivo (14) and it has been shown that fiuoride from a fiuoride-containing amalgam is taken up in enamel and dentine in vitro (15,16) and in vivo (17), This has an inhibitory effect on cavity wall lesions in vitro (18,19), A 2-yr clinical trial of fluoride-containing amalgam fillings in Norway showed that the addition of fiuoride to amalgam did not result in significantly more corrosion or marginal breakdown than occurs in conventional amalgam fillings (20), However, in that study caries incidence among the participants was low. and the • number of participants wa,>; small, so lhe study lacked the power to register an effect on secondary earies incidence.…”
mentioning
confidence: 99%